Finite element modeling of failure in a bond layer - Tan, Hou Soon. (2012)
Technology advancement in the electronic and electrical industry has been a crucial factor in the development and enhancement of the modern living standard. Highly-intelligent electronic products were introduced to establish the connection with the power of Information Technologies (IT). The investigation on the mechanical properties of the fundamental components in a common electronic product became crucial and, thus, the solder joint will be studied for its strength that determines the durability and functionality of the product. In this report, the mechanical properties and material behaviors of Sn-3.8Ag-0.7Cu (SAC387) solder specimens were tested and discussed for a range of geometrical ratios and strain rates at room temperature. For the first experiment, the copper rod specimens were machined and soldered with the desired SAC387 based on their specified geometrical ratio and then tested with an uni-axial load at a constant strain rate of 0.01s-1. Comparisons were firstly conducted between the experimental and theoretically calculated results based on Orowan’s Approximation Equation. Then, the experimental results were also compared against the Finite Element Analysis (FEA) simulation results. Based on the experiment, it was observed that variation of the geometrical ratio induced the formation of the dimensional constraining effect within the material, which resulted in the linear relationship towards the Ultimate Tensile Strength (UTS) of the SAC387. Within the geometrical ratio, it was also studied that the variation in the thickness of the joint had caused higher influence towards the UTS of the SAC387 as compared to varying the diametric dimension.